2006
DOI: 10.1007/s10569-006-0001-2
|View full text |Cite|
|
Sign up to set email alerts
|

Report of the International Astronomical Union Division I Working Group on Precession and the Ecliptic

Abstract: The IAU Working Group on Precession and the Equinox looked at several solutions for replacing the precession part of the IAU 2000A precession-nutation model, which is not consistent with dynamical theory. These comparisons show that the (Capitaine et al., Astron. Astrophys., 412, 2003a) precession theory, P03, is both consistent with dynamical theory and the solution most compatible with the IAU 2000A nutation model. Thus, the working group recommends the adoption of the P03 precession theory for use with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 13 publications
(4 reference statements)
0
34
0
Order By: Relevance
“…The IERS should take appropriate measures, in conjunction with the IAU Working Group on reference frames, to maintain the ICRF and its ties to the reference frames at other wavelengths. [J. L. Hilton et al 2006], and recommends that the terms lunisolar precession and planetary precession be replaced by precession of the equator and precession of the ecliptic, respectively, and that, beginning on 1 January 2009, the precession component of the IAU 2000A precession-nutation model be replaced by the P03 precession theory [Capitaine et al 2003] in order to be consistent with both dynamical theories and the IAU 2000 nutation. (2006) is a supplement to the IAU 2000 resolutions on reference systems, containing primarily two recommendations, the first to harmonize the name of the pole and origin to "intermediate" and a second recommendation fixing the default orientation of the BCRS and GCRS, which are assumed to be oriented according to the ICRS axes (for more information see the IERS Conventions 2010 [Petit et al 2010]).…”
Section: Iugg Resolution No 2 (1991) On the Conventional Terrestrialmentioning
confidence: 99%
“…The IERS should take appropriate measures, in conjunction with the IAU Working Group on reference frames, to maintain the ICRF and its ties to the reference frames at other wavelengths. [J. L. Hilton et al 2006], and recommends that the terms lunisolar precession and planetary precession be replaced by precession of the equator and precession of the ecliptic, respectively, and that, beginning on 1 January 2009, the precession component of the IAU 2000A precession-nutation model be replaced by the P03 precession theory [Capitaine et al 2003] in order to be consistent with both dynamical theories and the IAU 2000 nutation. (2006) is a supplement to the IAU 2000 resolutions on reference systems, containing primarily two recommendations, the first to harmonize the name of the pole and origin to "intermediate" and a second recommendation fixing the default orientation of the BCRS and GCRS, which are assumed to be oriented according to the ICRS axes (for more information see the IERS Conventions 2010 [Petit et al 2010]).…”
Section: Iugg Resolution No 2 (1991) On the Conventional Terrestrialmentioning
confidence: 99%
“…Effective Jan 1, 2009, the IERS recommends the use of the new International Astronomical Union (IAU) models for nutation and precession to perform this GCRF/ITRF transformation. [3,22,23,24,25,26,27 [3,5,28].…”
Section: Gcrf/itrf Transformationmentioning
confidence: 99%
“…The value is taken from Capitaine et al (2005). A discussion about the uncertainty can be found in Bourda and Capitaine (2004) and in Hilton et al (2006) while a discussion about the components of the J 2 variation can be found in Cheng and Tapley (2004) with a 2008 AGU update (2008AGUFM.G33A0673C).…”
Section: Time Rate Of Change In Jmentioning
confidence: 99%
“…Obliquity of the ecliptic at J2000.0, J2000 The obliquity of the ecliptic at J2000.0, J2000 , is from the Hilton et al (2006) report from the IAU Working Group on precession and the ecliptic. This value is taken from the P03 precession model of Capitaine et al (2003) and was adopted in IAU 2006 Resolution B1.…”
Section: Ratio Of the Mass Of (4) Vesta To The Sun M Vesta /M Smentioning
confidence: 99%